La "Do\~na" è mobile: The role of women in social mobility in a premodern economy - José-Antonio Espín-Sánchez; Salvador Gil-Guirado; Chris Vickers (Yale University, Economic Growth Center, 2020)
We use data from marriage records in Murcia, Spain, in the 18th century to study the role of women in social mobility in the pre-modern era. Our measure of socioeconomic standing is identification as a don or do\~na, an honorific denoting high, though not neccesarily, noble status. We show that this measure, which is acquired over the lifecycle, shows gendered transmission patters. In particular, same-sex transmission is stronger than opposite-sex, for both sons and daughters. The relative transmission from fathers versus mothers varies over the lifecycle, and grandparents may have an effect on the status of their grandchildren.
Keywords: D31; J62; N33; 330; Social mobility; Spain; Assortative mating; Marriage; Status